A Transmit Beamforming and Nulling Approach with Distributed Scheduling to Improve Cell Edge Throughput. (1st February 2010) - Wong, Wendy C.; Li, Qinghua; Talwar, Shilpa
Abstract : We propose a transmit scheme for WiMAX systems, where multiple base stations (BSs) employ downlink transmit beamforming and nulling for interference mitigation, with minimal coordination amongst BSs. This scheme improves system throughput and robustness, by increasing cell edge and overall cell throughputs by 68% and 19%, respectively, and by delivering improvement for mobile speed up to 60 km/h. First, cell edge users suffering from severe interferences are identified. Next, the RRM unit allocates resource to serving cell edge users only. BSs will schedule to serve their cell edge users independently using the allocated resources by the RRM. A special uplink sounding region is designed for BSs to learn the interference environment and form proper beams and nulls. The nulls formed towards users served by other BSs reduced interference from a BS towards these users and is the basic building block of our algorithm.